If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + -15 = 6(2b + 5) Reorder the terms: -15 + -3b = 6(2b + 5) Reorder the terms: -15 + -3b = 6(5 + 2b) -15 + -3b = (5 * 6 + 2b * 6) -15 + -3b = (30 + 12b) Solving -15 + -3b = 30 + 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. -15 + -3b + -12b = 30 + 12b + -12b Combine like terms: -3b + -12b = -15b -15 + -15b = 30 + 12b + -12b Combine like terms: 12b + -12b = 0 -15 + -15b = 30 + 0 -15 + -15b = 30 Add '15' to each side of the equation. -15 + 15 + -15b = 30 + 15 Combine like terms: -15 + 15 = 0 0 + -15b = 30 + 15 -15b = 30 + 15 Combine like terms: 30 + 15 = 45 -15b = 45 Divide each side by '-15'. b = -3 Simplifying b = -3
| 3(x+21)=-4(x-21) | | 4x+6=3x+2 | | 9(x-4)=3x+6 | | 17=-4x | | 7(x-3)=5x+-7 | | 5(x+2)=2x+19 | | 17-5x=22+4x | | -9x-6x=150 | | 23=2x+6 | | 2x^2-4x-14=0 | | 5-x+2=10 | | -9x-6x=159 | | 23-2x=4x+6 | | y=-4x^2+12x+40 | | 3x-18+15=4x-4+4 | | 3x=5.5 | | -5d-6=-14 | | 5+2x+1=7 | | 4y+2=3y+4 | | 5d-12=-3 | | n=81jk^2 | | lnx^2-ln^5=0 | | 11x^4+42x^2-8=0 | | 4(12-8w)=18 | | 10x+11=-199 | | 7x+2=4x+9 | | 4x+5=1x-5 | | 8+12x=85+x | | -3(3s-6)-18=-3(6s+3)-3 | | 4x+5=5x-1 | | 18=6(w+4)-8w | | X(3+1)-5x=9 |